Korelasi Tingkat Penguasaan Mufrodat Dengan Kemampuan Menulis Kreatif Mahasiswa PBA IAIN Palangka Raya - Agustin, Eva; Wahdah, Nurul; Permana, Farid (The Arabic Education Department Postgraduate Programs, UIN Sultan Maulana Hasanuddin Banten in Partnership with PPJKBA Indonesia, 2024)
This study aims to determine 1) the level of vocabulary mastery of students of Arabic language education study program. 2) the creative writing skills of students of Arabic Education study program. 3) the relationship between the level of vocabulary mastery and creative writing skills of students of Arabic Language Education Study Program. This study used a correlational method with a quantitative approach. Data were collected through documents and tests of vocabulary mastery and creative writing skills. The sample of this study consisted of 22 students of the Arabic language education study program in the 4th semester who had undergone creative writing courses. The results showed that 1) students' vocabulary mastery had an average score of 79.55 with a good category. 2) Students' writing skills have an average score of 71.23 with a good category as well. 3) There is no significant correlation between the level of vocabulary mastery and creative writing skills of students of the Arabic Language Education Study Program at the Palangka Raya State Islamic Institute with a sig. (2-tailed) value of 0.178>0.05 and the correlation coefficient value is 0.298 which is at the level of a moderate positive correlation relationship.